ANALISIS DAYA SAING EKONOMI KABUPATEN/KOTA DI PROVINSI KALIMANTAN BARAT - B2051141001, SYAHRAN NUR (Jurnal Ekonomi Daerah (JEDA), 2016)
This study entitled  "Analysis of Economic Competitiveness Regency/City in West Kalimantan Province.  It’s  aiming to known  and analyze the economic competitiveness of the 14 districts/ municipalities in West Kalimantan Province. Using 10 (ten) variable of  macroeconomic indicator on average over the four years 2010 to 2013, that taken from the BPS published of districts/mocipalities and provinces. The method of this analysis by performing the weighted ranking of each economic variable on each district / city. The rated (rangking) competitiveness of district / city is the sum (Σ) weighted ranking of each region of  the lowest (1x10) to the highest (14x10). In the assessment used a range between 0 (zero) to 100 (one hundred) so the scale or range of ratings to 7.14 (lowest) to 100 (highest), then within that range are classified into five categories that are very strong, strong, moderate, and low or weak. The results showed the area that has the highest competitiveness or the most powerful is the city of Pontianak as having economic competitiveness most powerful (category A), Ketapang as having economic competitiveness strong (category B) it’s almost up to A category. Sambas district competitiveness is powerful economies (category B) it position of the area above the average value of economic competitiveness of Kalbar and Landak regency that have economic competitiveness Medium (category C) as the area is in a position below the average value system of economic competitiveness. While Kayong Utara Regency most competitive economy Medium (category C) but almost up in B category, and Melawi Regency is  the only region in West Kalimantan with weak (lowest)  competitiveness (category D). An area that has strong competitiveness is very strong and shows that areas with strong economic resilience, is not easily shaken by conditions or events such as a crisis or other macro-economic problem/disease. While areas with low competitiveness indicate that the area is prone to shocks and economic crisis. Keywords   : “economic competitiveness, competitiveness ranking, macroeconomic, regional characteristics.